2019
DOI: 10.1590/0103-8478cr20180803
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids stability in goat yoghurt

Abstract: Evaluation of fatty acids (FAs) stability in dairy products undergoing technological milk processing is important for subsequent determinations of nutritional value. The aim of the study was to assess FA composition in milk and its dairy product and to explore differences in the FA profile found in yoghurt compared to raw material (goat milk). In the present study, a reduced proportion of volatile FAs (VFA) that cause “goat flavor” was reported in goat yoghurt in comparison to the FA profile of milk. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Domagala et al [53] found a non-significant effect on long chain fatty saturated acids in fermented milk stored at 4°C for 15 days. Changes were observed in the fatty acid profile of goat milk and yogurt during processing as described by [54]. Similar results about the decrease in tendency of myristic and palmitic acids were also observed in yogurt fatty acid profile when yogurt fat was replaced with rose hip seed oil [55].…”
Section: Discussionsupporting
confidence: 77%
“…Domagala et al [53] found a non-significant effect on long chain fatty saturated acids in fermented milk stored at 4°C for 15 days. Changes were observed in the fatty acid profile of goat milk and yogurt during processing as described by [54]. Similar results about the decrease in tendency of myristic and palmitic acids were also observed in yogurt fatty acid profile when yogurt fat was replaced with rose hip seed oil [55].…”
Section: Discussionsupporting
confidence: 77%
“…However, previous studies with milk or cream fermentation provided controversial data. It has been reported that LAB starters and probiotic bacteria were associated with increases in MCFA content in various fermented dairy products (Gassem et al ., 2016; Pecová et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This could explain the considerable decrease in the vitamin A content of YS, noted in the current study, because YS was packaged in a glass jar and exposed to light. The fatty acid profile of yogurt is affected by the concentrations of fatty acids in milk used in the production process (Pecová et al 2019). The lipolytic activity of lactic acid bacteria in yogurt is limited, and therefore it exerts a minor impact on the fatty acid profile (Ribeiro et al 2011, Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%